Nurses’ attitudes about RSV vaccination for pregnant women and infants: Evidence from a cross-sectional survey - Filip Viskupič; David L. Wiltse; Thomas E. Stenvig (PLoS ONE, 2025)
Respiratory syncytial virus (RSV) vaccines for pregnant women and infants became available in 2023 in the United States. However, the uptake of these vaccines has been low. Nurses play an important role in provider-patient vaccine communication. We conducted a survey on nurses’ attitudes about whether pregnant women and infants should receive an RSV vaccination. We distributed a survey to nurses in South Dakota, United States in May 2024. We used multivariate ordered logistic regression to determine the factors influencing nurses’ attitudes toward RSV vaccination. We received 1,908 responses; 44% of participants agreed that pregnant women should receive an RSV vaccination, and 72% agreed that infants should do so. The agreement was associated with personal vaccination status, age, education, and partisan self-identification. Among nurses 60 years and older, the agreement was associated with personal RSV vaccination uptake. Participants were more supportive of infants receiving RSV vaccine than pregnant women. The nurses who attained lower education status, did not receive COVID-19 and flu vaccinations, and identified as Republican or independent were less likely to think that pregnant women and infants should receive RSV vaccination. Strengthening provider knowledge about RSV vaccines for pregnant women and infants can help increase RSV vaccine uptake.